حكام الإمارة الأغلبية وإنجازاتهم في إفريقية "184-296 هـ. / 800-909 م." - بوصيفع، سامية (جامعة العربي التبسي تبسة - مخبر الدراسات الإنسانية والأدبية, 2024)
بعد انقضاء عصر الولاة قامت عدة دويلات وإمارات إسلامية ببلاد المغرب منها إمارة الأغالبة (184-296 هـ 800- 909 م)، التي شملت حدودها تونس حاليا وجزء من شرق الجزائر، وهي إمارة استكفاء عن الخلافة العباسية حكمها وأدار شؤونها 11 أميرا أغلبيا، أولهم الأمير إبراهيم بن الأغلب سنة 184 هـ/ 800 م وآخرهم الأمير أبي مضر زيادة الله الثالث بن عبد الله الأغلبي سنة 290 هـ/ 903 م. وقد كان لهم الدور الفعال في المنطقة؛ منها في الجانب العمراني بناؤهم المدينة رقادة والعباسية وإنشاؤهم العديد من المواجل والقناطر بالإضافة إلى المساجد والأسواق والحمامات وكذا الفنادق وأقاموا الرباطات والمحارس، كما كونوا عسكريا قوة عسكرية شكلت الجيش الأغلبي في البر والأسطول في البحر، وفي مجال الصناعة صنعوا أدوات الحرب والسفن التي كونوا بها أسطولهم لفتح صقلية وغيرها من المناطق؛ كما لم تخرج الزراعة من مجال اهتمامهم فشجعوا الفلاحين ودعموهم بمختلف الوسائل اللازمة، فتنوعت المحاصيل الزراعية وتحقق الاكتفاء الذاتي فتم تصدير الفائض من المنتوج إلى خارج الإمارة. After the end of the governors ages alwullat, many Islamic emirates emerged, including the Aghalib emirate which presents Tunisia and part eastern Algeria today. This emirate was affiliated with the Abbasid caliphate in Baghdad, it was ruled by eleven princes, the first of whom was Prince Ibrahim ibn Al-ghlab in 800 AD and the last of them was prince Abu mudur ziyadat allah the third Ibn abdullah Al-aghlabi in 903 AD. The Aghlabi’s state had an important role in the Islamic Maghreb and the western basin Mediterranean where they left many architectural achievements such as the city of Raqqada and abbasid they established money coasts and arches, also they built mosques, Markets, Baths and hotels in addition to the Ribats and guardians they formed a land and sea military force. As for industry they made war tools and ships from with they built their fleet which enabled them to conquer Sicily and many regions in the Mediterranean. The agriculture was also one of their concerns, they supported farmers with various means and facilities they made watering facilities as a result agricultural crops were diversified self-sufficiency was achieved and surplus products were exported outside the emirates whether to neighboring countries or Andalusia and the Orient
Keywords: الإمارات الإسلامية -- الدولة الأغلبية -- حكام إمارة الأغالبة